AVIATION BENCHMARKING IN THE TRAINING SYSTEM OF SPECIALISTS IN THE FIELD OF LAW - Bezzubov, Dmytro; Kuz, Kateryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Goal: consideration of the issue of aviation benchmarking as an element of the training of lawyers in the field of aviation, determination of the degree of influence of institutional and technical tools on the state of training of lawyers in the field of aviation and their actual readiness to perform tasks to ensure aviation safety. Research methods: scientific methods of system analysis, formal logic and method of classifications. The method of system analysis is applied accordingly to determine the current state of legislation in the field of training lawyers. The method of formal logic made it possible to determine scientific views on the categories of legal elements of benchmarking in the field of aviation. The method of classifications made it possible to determine the ways of further improvement of institutional methods regarding the influence on the regulation of the training of legal specialists in the field of aviation from the standpoint of benchmarking. Results: research on the training of lawyers in the field of aviation from the standpoint of benchmarking allows to determine the ways and methods of minimizing the impact of negative factors and risks of the process of performing a flight task on the state of legal protection of participants in the flight process. The results of the research presented in this scientific article make it possible to determine further steps in the study of the problems of legal aspects of the formation and control of the training of legal specialists in the field of aviation. Discussion: the development of the science of legal pedagogy in the modern world is undergoing a stage of new formatting and philosophical rethinking. This is due to the new challenges facing this science in the conditions of scientific and technical development and the development of information technologies. Training of professional personnel taking into account the trend of globalization is one of the priority tasks in pedagogy as a science of personnel training. In the conditions of the development of scientific and technical progress, the training of legal specialists in the aviation field acquires an important importance due to the specifics of the activities performed by the crews of civil aircraft, their tasks and the conditions for performing the flight task. It should be noted that for the legal sphere, the fact that during the flight there are cases when the commander of the aircraft must conduct piloting under manual control conditions is important. At the same time, such piloting takes place in the conditions of threats, risks and dangers regarding the probability of loss of airworthiness by the aircraft, as a result of falling from the echelon and the death of passengers and crew members of the civil aircraft. In the modern method of training legal specialists, there are no clear and formal mechanisms for the formation of psychological stability in lawyers regarding the assessment of the consequences of disasters and familiarization with cases related to the death of people. Therefore, the formation of training methods for legal specialists in the aviation field is one of the priority directions in pedagogy as a science of training highly qualified personnel for all spheres of society.